Inhibition of nitrogenase activity by NH+4 in Rhodospirillum rubrum. - Sweet, W J (1981)
Nitrogenase activities and the patterns of in vivo inhibition of nitrogenase by NH+4 were compared in Rhodospirillum rubrum grown under several conditions of nitrogen availability. In cells grown on N2 or glutamate plus N2, nitrogenase activity was relatively low and was totally inhibited by added NH+4 in 15 to 20 min. In contrast, cells grown on glutamate alone displayed higher nitrogenase activity, and NH+4 had very little effect. Cells grown on limiting amounts of NH+4 had lower nitrogenase activity, but NH+4 produced little inhibitory effect. Uptake of NH+4 could be demonstrated under all of these conditions, and this uptake was blocked by DL-methionine-dl-sulfoximine. The data indicated that cells not recently exposed to NH+4 had no mechanism for rapidly turning off nitrogenase activity in response to sudden additions of NH+4. In contrast, cells grown in the presence of N2, which form NH+4 internally, inhibited nitrogenase activity relatively quickly in response to added NH+4.